2014
DOI: 10.1002/pros.22750
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors influencing prostate cancer‐specific survival in non‐castrate patients with metastatic prostate cancer

Abstract: A longer PSA DT, involvement of nodes or axial skeleton and a lower number of metastases are associated with an improved PCSS in non-castrated patients developing metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(82 citation statements)
references
References 36 publications
1
80
1
Order By: Relevance
“…Also in our group OS was better than reported by Singh D. et al which suggest that use of SRS/SABR can result in prolongation of patients life despite other treatment options used [3]. Ost P et al reported that number of metastases correlates with OS and patients with only 1 lesion had 5-year OS of 90% (compared to 35% for patients with more than one lesion) but this correlation was of statistical significance in our group only in univariate analysis [15]. Published reports concerning local control of lesions after SRS/SABR are very promising.…”
Section: Discussioncontrasting
confidence: 61%
“…Also in our group OS was better than reported by Singh D. et al which suggest that use of SRS/SABR can result in prolongation of patients life despite other treatment options used [3]. Ost P et al reported that number of metastases correlates with OS and patients with only 1 lesion had 5-year OS of 90% (compared to 35% for patients with more than one lesion) but this correlation was of statistical significance in our group only in univariate analysis [15]. Published reports concerning local control of lesions after SRS/SABR are very promising.…”
Section: Discussioncontrasting
confidence: 61%
“…Patients with local recurrence [7] and patients with a limited number of metastases, so-called oligometastatic patients, have a much better prognosis than patients with extensive metastatic disease, as the oligometastatic cancer state is considered to be an intermediate state of tumour spread with limited metastatic capacity and less aggressive behaviour [8]. In analogy with other solid tumours, eradication of these tumour manifestations by means of metastases directed therapy (MDT) with radiotherapy is an emerging way to delay disease progression and postpone systemic treatment without major treatment toxicity [9].…”
Section: Introductionmentioning
confidence: 99%
“…There have been studies that suggest hormone-sensitive prostate cancer with oligometastasis may well be eligible for a similar approach given the remarkably favourable prognosis observed in men with oligometastasis. 12,13 Recently, a possible survival benefit of local therapy combined with ADT in metastatic patients has emerged. 14 Two review studies suggested that local or metastatic-directed radiotherapy are reasonable interventions as toxicity is minimal and decreases the necessity for subsequent palliative treatments.…”
Section: Cuaj -Case Series Cho Et Al: Testicular Oligometastasis Frommentioning
confidence: 99%